Self medicated Combiflam induced acute dermatological drug reaction - Singh, Harminder; Bala, Ritu; Kaur, Kamalpreet (International Journal of Basic & Clinical Pharmacology, 2017)
A 30 year old female took a single tablet of Combiflam (ibuprofen 400mg + paracetamol 325mg) for backache following which she noticed maculopapular rashes with generalized facial and lip swelling with generalized itching. Subsequently patient was treated with antihistaminic and steroids and she responded well. The causality assessment according to Naranjo casualty assessment scale come under “Probable” category of adverse drug reaction. According to World Health Organization-Uppsala Monitoring Centre causality assessment scale it falls under “Probable/Likely” category. According to Hartweig and Siegel severity assessment scale it was level 3 and moderate adverse drug reaction. This is a rare adverse effect of combiflam with the incidence less than 0.1%. The awareness of the health care personnel to this widely used drug on its rare adverse effect is necessary.